KEWENANGAN PENGAWASAN DAN PENGUJIAN TERHADAP PERATURAN DESA DITINJAU DARI PERSPEKTIF PERATURAN PERUNDANG-UNDANGAN - Lanang Sakti (Fakultas Hukum Universitas Mataram, 2016)
Judicial Regulatory Authority of the Village Seen From the Perspective Regulation Legislation. The enactment of Law No. 12 of 2011 Concerning the Establishment of legislation, giving a different interpretation of the location or position of Village Regulations. This is because the village regulation is no longer listed as one of the hierarchy of legislation. Regulatory village allegedly contrary to legislation on it, regency / municipal government can conduct testing of Village Regulations by monitoring known as the Executive Review, while the authority Testing Legislation under the Act held by the Supreme Court known the Judicial Review.Keywords : Monitoring, Testing, Village Regulations